A novel brushless de‐excitation system for synchronous generators using a buck chopper with a freewheeling discharge resistor - Gildas Martial Ngaleu; Aurélien Tamtsia Yeremou; Charles Hubert Kom; Samuel Eke; Arnaud Nanfak (IET Electric Power Applications)
Abstract A new de‐excitation system for advanced brushless excitation based on a synchronous generator is presented. The proposed system uses a discharge resistor in series with a freewheeling diode of a buck chopper. It improves the reliability of the entire power plant and can be used on several excitation systems. It can be used in case of programmed shutdown of the generator and also shows good results in voltage regulation without destroying the efficiency of the excitation system under nominal operation. An analysis of the system has allowed us to suggest a methodology to obtain the appropriate value of the discharge resistance to be used. The validation of the proposed system has been done through simulations in the Matlab/Simulink environment, supported by experimental tests.